THE ROLE OF VIRTUAL MUSEUM IN PROMOTING RELIGIOUS TOURISM IN JORDAN - Issam Mohammad AL-MAKHADMAH (Geo Journal of Tourism and Geosites, 2020)
The religious motivation is one of the important reasons that drive tourists to travel with the intention of visiting the holy place. However, many obstacles still stand in the way of access to the holy places due to the religious privacy of some places where only non-followers are allowed to visit those places. This study reviews the hypothesis of setting up virtual museums of holy religious sites in Jordan to meet two goals; the first is to overcome the religious privacy of some Islamic or Christian holy places, and the second goal is to give an opportunity for all followers of religions to see the holy places of others. The results of the study showed that the idea of virtual museums represents the ideal solution for the tourist promotion of religious tourist places, and that virtual museums contribute to overcoming obstacles related to religious privacy, which provides an opportunity to see those places.